Evaluation of Phylogenetic Tree of blaCTX-M Gene in Pseudomonas earugenosa Isolated form Corneal Scraping Specimens in Baghdad - Ali Mhana Sabeeh Zirjawi (Journal of Global Pharma Technology, 2016)
Nosocomial infections caused by Pseudomonas earugenosa (P. earugenosa) presenting resistance to beta-lactam drugs are one of the most challenging targets for antimicrobial therapy, leading to substantial increase in mortality rates in hospitals worldwide. In this context, P. earugenosa isolates that isolated form Ibn-Al Haitham teaching hospital for eyes diseases had carried blaCTX-M gene which have the highest clinical impact. Hence, this study was designed to investigate the presence of genes codifying for bla CTX-M among beta-lactam resistant P. earugenosa isolated in one of Baghdad hospitals. Antibiotic sensitivity was carried out using Kirby-Bauer method, and polymerase chain reaction was carried out in addition to the gell electrophoresis, the genotypic and the sequencing in aadtion the phylogetic tree were done. Thirteen P. aerogenosa isolates were isolated from corneal scraping specimens and the results of antibiotic sensitivity showed that the most effective antibiotic on P. aerogenosa isolates was impeniem with 13(100%) sensitivity rate while the highest resistance was to cefozlen 13(100%) resistance rate. The investigation of the blaCTX-M gene via polymerase chain reaction showed the presence of blaCTX gene (544bp) in 3(23.1%) P. aerogenosa isolates. The sequencing of blaCTX-M amplicons confirmed the correct identification of blaCTX-M gene among P. aerogenosa isolates and the data obtained from the sequencing of blaCTX-Mgene was submitted to the GenBank of National Center for Biotechnology Information (NCBI) under the accession number (KY966041). Molecular phylogenetic analyses were based on the sequences of blaCTX gene and closest relatives (100% identity) with closely related blaCTX-M gene of some bacterial isolates in the GenBank by using MEGA6 software.Keywords: Pseudomonas aerogenosa, blaCTX M gene and phylogetic tree.